Analysis of HIV Cases in West Java Province 2019-2023 - Rahmadani, Hevaf; Nurhayati, Siti Fatimah (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze how socioeconomic factors affect HIV prevalence in West Java Province from 2019 to 2023. The variables examined include poverty, unemployment, the Human Development Index (HDI), and health facilities. Using a quantitative approach with panel data regression on 27 districts/cities, the Fixed Effect Model (FEM) results show that HDI and health facilities significantly influence HIV prevalence, while poverty and unemployment have no significant effect. The coefficient of determination (R²) of 0.6930 indicates that 69.30% of HIV rate variations are explained by the model's variables, with the remainder influenced by other factors. These findings highlight that improving the Human Development Index and expanding health facilities play a crucial role in reducing HIV prevalence across West Java Province.